Pengaruh Tingkat Inflasi terhadap Penyaluran Kredit pada PT Pegadaian Syariah Cabang Meulaboh - Nadila, Rahma; Jalil, Ivon (Medan Resource Center, 2022)
This article aims to discuss the influence of the inflation rate on lending at PT Pegadaian Syariah Meulaboh Branch. PT. Pegadaian Syariah is committed to providing the best and most useful service for every customer which is manifested through the professional attitude and response of the company and its range of staff in serving customers. Pegadaian also guarantees the quality of service to every customer in a swift, responsive and reliable manner. Through various services, PT. Pegadaian Syariah helps consumers guarantee the quality and safety of their product risks and reduces and fulfills consumer expectations. Inflation is a scourge for many credit service providers to continue distributing their facilities. In this study, the purpose of the study was to see how far the credit service policy still applies to PT. Pegadaian Syariah even though inflation continues. This research took place at PT. Pegadaian Syariah Meulaboh Branch with 113 research samples and the results obtained were that PT. Pegadaian Syariah continues to process financial credit even though inflation occurs even under severe conditions.